An image and video dataset of nesting green sea turtles with annotated data - Irwandi, Hipiny; Hamimah, Ujir; Ruhana, Hassan; Abang Arabi, Abang Aimran (Nature, 2024)
Photo- and video-based reidentification of green sea turtles using their natural markers is far less invasive than artificial tagging. An RGB camera mounted on a man-portable rig, was used to collect video data on Greater Talang Island (1 °54’45′′N 109 °46’33′′E) from September to October 2022, and September 2023. This islet is located 30 minutes offshore from the Sematan district in Southwest Sarawak, Malaysia. In total, 42 videos of 42 unique individuals were captured, from which 14,471 video frames were extracted and annotated with a bounding box each. Through manual inspection, the annotation data were diligently checked and edited if necessary. Additionally, 130 selected frames were further annotated each with a region-of-interest mask containing only the carapace. These data have the potential to aid researchers in training computer vision models for various tasks such as counting, segmentation and individual reidentification.